2022
DOI: 10.3390/biomedicines10061307
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profile and Pathological Alterations in the Muscle of Patients with Early-Stage Amyotrophic Lateral Sclerosis

Abstract: Diverse biomarkers and pathological alterations have been found in muscle of patients with Amyotrophic lateral sclerosis (ALS), but the relation between such alterations and dysfunction in energetic metabolism remains to be investigated. We established the metabolome of muscle and serum of ALS patients and correlated these findings with the clinical status and pathological alterations observed in the muscle. We obtained data from 20 controls and 17 ALS patients (disease duration: 9.4 ± 6.8 months). Multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 124 publications
1
5
0
Order By: Relevance
“…Specifically, dysregulated metabolites were linked to carbohydrate metabolism and amino acid pathways, previously associated with ALS [52]. Interestingly, mitochondrial dysfunctions are associated with metabolism deregulation in the muscles of ALS patients [51 ▪ ]. Because of the small cohort size, this study reinforces the need for more investigations into muscles of ALS patients at early stages.…”
Section: Early Involvement Of Metabolic Abnormalities In Amyotrophic ...supporting
confidence: 52%
See 1 more Smart Citation
“…Specifically, dysregulated metabolites were linked to carbohydrate metabolism and amino acid pathways, previously associated with ALS [52]. Interestingly, mitochondrial dysfunctions are associated with metabolism deregulation in the muscles of ALS patients [51 ▪ ]. Because of the small cohort size, this study reinforces the need for more investigations into muscles of ALS patients at early stages.…”
Section: Early Involvement Of Metabolic Abnormalities In Amyotrophic ...supporting
confidence: 52%
“…Mutant SOD1 mouse models demonstrated early metabolic reprogramming in glycolytic muscles associated with mitochondrial dysfunctions [49,50]. In ALS patients, only one recent study explored muscle-specific metabolic defects [51 ▪ ]. At the time of diagnosis, Lanznaster and collaborators observed alterations in the metabolome of skeletal muscles of ALS patients.…”
Section: Early Involvement Of Metabolic Abnormalities In Amyotrophic ...mentioning
confidence: 99%
“…Patients with SOD1and C90RF72-induced ALS show abnormal glucose metabolism and hypometabolism or hypermetabolism in different brain regions depending on pathological involvement [50]. Some researchers have reported alterations in the muscle metabolome, particularly abnormal metabolites related to carbohydrate metabolism and the amino acid pathway in patients with ALS [51,52]. This study demonstrated that mitochondria impairment is involved in muscle glycolysis, leading to ATP reduction.…”
Section: Discussionmentioning
confidence: 56%
“…RD2RD2 seems to bring a benefit in instantaneous muscle strength rather than in unremitting muscle endurance pointing to a hindered effect of RD2RD2 under anaerobic muscle conditions. This might also exclude an effect of RD2RD2 on the mitochondria and their oxidative metabolism which are known to be implicated in ALS [ 30 ].…”
Section: Discussionmentioning
confidence: 99%